Suku To Balo Dalam Kajian Geografi Budaya Di Kabupaten Barru - Arlina, Yuli (UNIVERSITAS NEGERI MAKASSAR, 2018)
This research was conducted with the aim to know the characteristics of the To Balo Tribe's life pattern in the village of Bulo-BuloPujananting Sub-district of Barru Regency, the social relationship of To Balo Tribe with the surrounding community. The type of research is qualitative research with Ethnography approach. The results showed that, their To Balo Tribe lives cooking, cultivating yams, corn, and beans, farming and processing palm sugar. In the dry season they grow peanut plants that do not really need water. In addition to farming, To Too tribe also raises ducks, chickens, and cattle. To Balo interaction with the people around the beginning was not good To Balo did not want to mingle, due to feel ashamed then To Balo not out of the settlement, the local community is not disturbed To To Balo but over the development time To Balo is open and willing to blend, even have often to the city each week with the Bulo-Bulo community and mingle as well if there is an invitation to a party or a show of salvation. Suggestions that will be compilers give is the existence of Tribe To Balo in the future is still maintained and protected from extinction and non To Balo people can live together, and still high up the local cultures and wisdom and in the guarding and preservation of To Balo Tribes is very in need, because it will impact on the object directly.